Análisis de la temperatura superficial en una losa de concreto en exposición ambiental en la ciudad de Bogotá (2024)
An investigation was carried out on the influence of environmental factors on a concrete slab given that concrete structures present a significant problem in which stability is affected and their durability can also present cracks and humidity. The plate is located in the city of Bogotá where 2 daily data were collected using the thermographic camera where the following parameters were evaluated: upper and lower temperature of the concrete slab; This data collection was carried out for a period of 20 days, after which the respective analyzes of these data were carried out in a program where the maximum and minimum temperature values were obtained as a result.